Phytochemical Screening and Antiprotozoal Effects of the Methanolic Berberis Vulgaris and Acetonic Rhus Coriaria Extracts - Gaber El-Saber Batiha; Amany Magdy Beshbishy; Oluyomi Stephen Adeyemi; Eman Hassan Nadwa; Eman kadry Mohamed Rashwan; Luay M. Alkazmi; Amr A. Elkelish; Ikuo Igarashi (Molecules, 2020)
Berberis vulgaris (B. vulgaris) and Rhus coriaria (R. coriaria) have been documented to have various pharmacologic activities. The current study assessed the in vitro as well as in vivo inhibitory efficacy of a methanolic extract of B. vulgaris (MEBV) and an acetone extract of R. coriaria (AERC) on six species of piroplasm parasites. The drug-exposure viability assay was tested on three different cell lines, namely mouse embryonic fibroblast (NIH/3T3), Madin-Darby bovine kidney (MDBK) and human foreskin fibroblast (HFF) cells. Qualitative phytochemical estimation revealed that both extracts containing alkaloid, tannin, saponins and terpenoids and significant amounts of flavonoids and polyphenols. The GC-MS analysis of MEBV and AERC revealed the existence of 27 and 20 phytochemical compounds, respectively. MEBV and AERC restricted the multiplication of Babesia (B.) bovis, B. bigemina, B. divergens, B. caballi, and Theileria (T.) equi at the half-maximal inhibitory concentration (IC50) of 0.84 ± 0.2, 0.81 ± 0.3, 4.1 ± 0.9, 0.35 ± 0.1 and 0.68 ± 0.1 µg/mL and 85.7 ± 3.1, 60 ± 8.5, 90 ± 3.7, 85.7 ± 2.1 and 78 ± 2.1 µg/mL, respectively. In the cytotoxicity assay, MEBV and AERC inhibited MDBK, NIH/3T3 and HFF cells with half-maximal effective concentrations (EC50) of 695.7 ± 24.9, 931 ± 44.9, >1500 µg/mL and 737.7 ± 17.4, >1500 and >1500 µg/mL, respectively. The experiments in mice showed that MEBV and AERC prohibited B. microti multiplication at 150 mg/kg by 66.7% and 70%, respectively. These results indicate the prospects of these extracts as drug candidates for piroplasmosis treatment following additional studies in some clinical cases.